Penerapan Kegiatan Daur Ulang pada Anak sebagai Strategi Edukatif dalam Menumbuhkan Kesadaran Lingkungan - Fadilla Lestari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This community service aims to implement recycling activities for children as an educational strategy to foster environmental awareness from an early age. In the context of increasing environmental challenges, environmental education is an urgent need to shape a caring and responsible character for environmental sustainability. The method used is participatory learning with direct practice of recycling waste that actively involves children, accompanied by education on waste management, sorting, and the reuse of used materials into useful products. This approach uses observation, and documentation as data collection techniques to evaluate children's understanding and behavior. The results of the community service show a significant increase in children's awareness and concrete actions in protecting the environment after participating in the recycling activity. Children not only understand the concept of environmental conservation theoretically, but also practice it in their daily lives, such as sorting waste and reducing plastic waste. This community service's contribution to the development of science in the field of education lies in the successful implementation of an experiential learning model that integrates cognitive, affective, and psychomotor aspects in instilling environmental values. This educational model enriches an effective and contextual approach to environmental education, while also providing a strategic alternative for fostering environmental awareness among the younger generation. Thus, this community service makes a significant contribution to the development of educational methods that can strengthen sustainable development through the active participation of children from an early age.